Energy storage materials and super energy storage devices

By using the cellulose material made of wood or plant fibers, the nano -dimensional bumps on the surface use the quantum size effects, solve the problem that traditional capacitors are difficult to take into account between high -accumulation capacity and small volume, and achieve high efficiency and environmental protection Capacitor design.

CN115053309BActive Publication Date: 2025-01-28TOHOKU UNIV +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180013485.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-02-18
Filing Date
2021-02-12
Publication Date
2025-01-28
Estimated Expiration
2041-02-12

AI Technical Summary

Technical Problem

In the prior art, solid electric double layer capacitors have not been used yet, and traditional capacitors are difficult to take into account between high storage capacity and small volumes, and there is a risk of using combustible elements or environmental pollutants.

Method used

The crystallization or non -fixed fiber material made of wood or plant fibers (pulp) is used to form a high power storage capacity by forming nano -dimensional bumps on its surface.

Benefits of technology

It has achieved high -capacity, low -cost, and environmental protection characteristics under DC and AC, and can storage power in an instant or short time, suitable for various electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115053309B_ABST
    Figure CN115053309B_ABST
Patent Text Reader

Abstract

The present invention provides a storage material and a super storage body that are made of fiber materials of cellulose molecules obtained from wood, plant fiber (pulp), etc., and are capable of storing electricity under direct current and alternating current. The storage material has a fiber material and has countless bumps on the surface, and the fiber material is mainly composed of fibers from at least one of wood, plant fiber (pulp), animals, algae, microorganisms, and microbial products. The fiber material is preferably a crystallized amorphous fiber, preferably an amorphous fiber with atomic vacancies, and its specific surface area is preferably 10m 2 / g or more. The diameter of the countless concavities and convexities is preferably 1nm to 500nm. In addition, the resistance is preferably 100MΩ or more, and the capacitance is preferably 5mF / cm 2 above.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to an electric storage material and an ultrapower storage body. Background Art

[0002] Capacitors (large-capacity capacitors, capacitors) are electronic components that use electrostatic capacitance to store or release electric charge (electric energy). They play the role of power stabilizer, backup circuit, coupling element, noise filter, etc. in mobile electronic devices such as personal computers and mobile phones, and are indispensable components in electronic devices. In recent years, high-performance IT products such as mobile phones and ultra-small storage devices and batteries for electric vehicles have made rapid progress, and the demand for capacitors with smaller size, larger capacity and high functions such as memory effect has been increasing. In particular, there is a search for a product suitable for the era of smart grids (next-generation grids) that conforms to the concept of green innovation (low carbonization) to prevent global warming. For example, the market for capacitors for automobiles, IT equipment, energy-saving inverters, etc. has been steadily expanding at an average annual growth rate of about 3.7%, and has reached a trillion yen market.

[0003] As such a capacitor, it is desirable not to use flammable elements such as lithium or environmentally polluting substances. In other words, a material which is solid rather than liquid, harmless to health, and inexpensive is sought.

[0004] Capacitors are roughly divided into capacitors for high-voltage power supply circuits (strong current) and capacitors for electronic and electrical equipment circuits (weak current) according to their use. Among them, ceramic capacitors are mainly used as capacitors for electronic and electrical equipment circuits in the weak current field, and rechargeable batteries are also widely used as power storage devices such as mobile phones. In contrast, capacitors for strong current fields have not yet been put into practical use due to their insufficient voltage resistance and storage capacity.

[0005] In the past, capacitors using lumped-parameter circuits were used as main components of electronic and electrical equipment in a wide range of 1pF to tens of mF. The storage capacity C (F) is expressed as follows:

[0006] C = Q / V = ​​ε × (A / d)

[0007] (Wherein, Q: charge, V: voltage, ε: dielectric constant, A: electrode area, d: distance between electrodes).

[0008] Therefore, the larger the electrode area and the smaller the distance between electrodes, the higher the storage capacity can be. However, from the perspective of the miniaturization of electronic and electrical equipment and the required storage capacity, it is difficult to achieve a maximum capacity by increasing the electrode area A and reducing the distance d between electrodes, and it is also difficult to achieve a minimum capacity by reducing the electrode area A and increasing the distance d between electrodes. In addition, for capacitors with dielectric specifications based on current lumped parameter circuits, the electrostatic capacitance has reached saturation.

[0009] As a method of storing electricity with a higher capacitance than before, there is a method using an electric distributed parameter circuit. For example, recently, an electric double layer capacitor made by wetting an electric field solution in activated carbon has been put into practical use. However, a solid-based electric double layer capacitor has not yet been put into use.

[0010] Regarding solid energy storage materials, the inventors of the present application have found that Si-(Al, Ti, V) alloys, TiO2-coated Ti-Ni-Si and Al2O3-coated Al-Y amorphous alloys with Al, Ti, and V extracted and removed from the surface can store electric charges regardless of whether it is direct current or alternating current (for example, see non-patent documents 1 to 7 and patent documents 1 to 4).

[0011] In addition, the inventors of the present application have also found that when the compound particles are less than 40nm, preferably less than 10nm, the electron shielding occurring on the surface of nano-sized solids will cause a "quantum size effect". As a storage material utilizing this phenomenon, the inventors of the present application have developed a storage material that forms nano-sized bumps on the surface of amorphous titanium dioxide, amorphous aluminum oxide, and amorphous fluoropolymers (for example, see non-patent documents 4, 7 to 9, and patent document 4). For these storage materials, the van der Waals electrostatic force acts at the negative sixth power of the diameter of the convex portion. Due to the quantum nano-size effect, when the diameter of the convex portion is nano-sized and the smaller the diameter of the convex portion, the greater the ability of the convex portion to absorb electrons (for example, see non-patent document 7). Regarding the work function, which is a measure of the size of the electron absorption capacity, amorphous titanium dioxide is 5.5eV (for example, see non-patent document 7), and amorphous fluoropolymers are 10.3eV to 13.35eV (for example, see non-patent document 4 and patent document 4).

[0012] Furthermore, as a material having a work function greater than those of the above-mentioned storage materials and capable of storing large amounts of electricity, the inventors of the present application have developed a storage material whose surface is composed of an amorphous material with AlO6 as the main component and has a plurality of bumps and depressions, wherein the diameter of the bumps and depressions is 0.1 to 50 nm and the height difference is 0.1 to 50 nm (for example, see non-patent document 9).

[0013] In addition, as a storage material, a physical rechargeable battery has been developed with a voltage of 1.5V, an electric power of 500Wh / L, a power density of 8kW / L, a cycle life of 100,000 times, and an operating temperature range of -25°C to +85°C (for example, see non-patent document 11). However, it is a storage material that forms an electron trap energy level in the band gap of a semiconductor and utilizes a Schottky junction that charges and discharges by filling the energy level with potential or leaving the energy level empty, and its voltage is limited to 1.5V.

[0014] The above capacitors are all artificial compounds of inorganic or organic compounds. At present, from the perspective of protecting animals and plants and protecting the global environment, the world is avoiding the production of artificial compounds that lead to an increase in carbon dioxide or the production of microplastics that cause marine pollution. From this perspective, it is in line with the current direction of global environmental protection to develop a biomass capacitor made of wood and plant fibers (cellulose) obtained from plants, etc., which has a small environmental load related to production and disposal, is lightweight, and has high elasticity.

[0015] At present, as an electrostatic capacity paper capacitor having a capacitance of 100 pF to 10 μF, there is a capacitor commercially available which is obtained by thinly coating capacitor paper having a thickness of 8 to 15 μm with lacquer, vacuum-evaporating metals such as nickel, aluminum, and zinc, and overlapping and winding two sheets of the capacitor paper obtained thereby and impregnating them with an impregnating agent. However, it uses vegetable oil or silicone oil as an impregnating agent, and is therefore a wet capacitor using an electric lumped parameter circuit (for example, see non-patent document 12).

[0016] Prior art literature

[0017] Non-patent literature

[0018] Non-patent document 1: M. Fukuhara, T. Araki, K. Nagayama and H. Sakuraba, "Electric storage in de-alloyed Si-Al alloy ribbons", EuroPhys. Lett., 2012, 99, 47001

[0019] Non-patent document 2: M. Fukuhara, "Electric Charging / Discharging Characteristics of Capacitor, Using De-alloyed Si-20AlAlloy Ribbons", Elect.Electr.Eng., 2013, 3(2), p.72-76

[0020] Non-patent document 3: M. Fukuhara and H. Yoshida, “AC charging / discharging of de-alloyed Si-Al-V alloy ribbons”, J. Alloys and Comp., 2014, 586, S130-S133

[0021] Non-patent document 4: M.Fukuhara, H.Yoshida, M.Sato, K.Sugawara, T.Takeuchi, I.Seki, and T.Sueyoshi, "Superior electric storage in de-alloyed and anodic oxidizedTi-Ni-Si glassy alloy ribbons", Phys.Stat.Sol.RRL, 2013, 7(7), p.477-480

[0022] Non-patent document 5: M. Fukuhara and K. Sugawara, "Electric charging / discharging characteristics of super capacitor, using de-alloying and anodic oxidized Ti-Ni-Si amorphous alloy ribbons", Nanoscale. Res. Lett., 2014, 9, p. 253

[0023] Non-patent document 6: M.Fukuhara and K.Sugawara, "Anodic oxidation of Ti-Ni-Siamorphous alloy ribbons and their capacitive and resistive properties", ThinSolidFilms, 2015, 595, p.1-4

[0024] Non-patent document 7: M. Fukuhara, T. Kuroda and F. Hasegawa, “Amorphous titanium-oxide supercapacitors”, Sci. Rep., 2016, 6, 35870

[0025] Non-patent literature 8: M. Fukuhara, T. Kuroda, F. Hasegawa and T. Sueyoshi, “Superiorelectric storage on an amorphous perfluorinated polymer surface,” Sci. Rep., 2016, 6, 22012

[0026] Non-patent document 9: M. Fukuhara, T. Kuroda, F. Hasegawa, T. Hashida, E. Kwon and K. Konno, “Amorphous aluminum-oxide supercapacitors,” EuroPhys. Lett., 2018, 123, 58004

[0027] Non-patent document 10: M. Fukuhara, T. Kuroda, F. Hasegawa, Y. Shirai, T. Suwa, T. Hashida, and M. Nishijima, "Amorphous titanium-oxide supercapacitors with high capacitance", EuroPhys. Lett., 2019, 128, 58001

[0028] Non-patent document 11: Nippon Mjicron Co., Ltd., secondary battery battery, 〈http: / / www.mjc.co.jp / product / index3.html〉

[0029] Non-patent document 12: Encyclopedia of Japan (Japanese Encyclopedia) "Paper Paper", Shogakukan, 1994, Volume 26

[0030] Patent Literature

[0031] Patent Document 1: Japanese Patent No. 6498945

[0032] Patent Document 2: Japanese Patent No. 6628241

[0033] Patent Document 3: Japanese Patent Application Publication No. 2016-134934

[0034] Patent Document 4: Japanese Patent Application Publication No. 2017-41578 Summary of the invention

[0035] Technical Problems to be Solved by the Invention

[0036] The energy storage material described in non-patent document 7 is amorphous titanium dioxide, the energy storage material described in non-patent document 9 is amorphous aluminum oxide, and the energy storage material described in non-patent document 8 is an amorphous polymer. They are characterized by having electrical insulator bumps on their surfaces, but all have the problem of being artificial products.

[0037] The present invention starts from these problems and focuses on the use of plant fibers that are friendly to the earth's environment and can be recycled. The purpose of the present invention is to provide a storage material and a super storage body that are made of fiber materials using cellulose molecules obtained from wood and plant fibers (pulp), etc., and can store electricity under direct current and alternating current.

[0038] Technical means to solve technical problems

[0039] The inventors of the present application have found that by using a material having nano-concave and convex surfaces such as cellulose fibers or pulp as its aggregates as a solid power storage material, a high power storage property can be exhibited. The inventors of the present application have focused on crystallized amorphous fibers with wood and plant fibers (pulp) as the main components, and have completed the present invention. For example, the inventors of the present application have found that by using crystallized amorphous fibers with a diameter of 1 to 30 nm generated by TEMPO catalytic oxidation or carboxymethyl (CM) treatment, a high power storage property can be exhibited due to the quantum size effect on its surface. That is, it means that nano-sized concave and convex surfaces are formed on crystallized amorphous fibers and aggregates composed of them, just like the previous amorphous titanium dioxide, aluminum oxide, and polymers. Furthermore, when they store electricity, the circuit is formed as a distributed parameter circuit, so a large-capacity power storage body can be formed by parallel integration. That is, as shown in formula (1), the storage capacity is accumulated in a manner proportional to the area. The total storage capacity C is the product of n nano-sized capacitors c. In addition, since cellulose molecules obtained by polymerizing β-glucose are easily formed into a sheet shape due to hydrogen bonding, it is suitable for the integration of nanocapacitors that are the basis of electric distributed parameter circuits.

[0040] [Mathematical formula 1]

[0041]

[0042] Furthermore, the inventors of the present application have paid attention to the molecular formula (C6H 10 O5) n The polysaccharide cellulose shown has an OH group. The inventors of the present application believe that the OH group has a positive dipole moment, in which positive charges are stored, and even if the amount of adsorbed charge on the surface increases, the positive charge can maintain electrical neutrality, thereby avoiding electrical breakdown. In addition, regarding the positive dipole moment, it was also found that if the H of the carboxyl group COOH at the end of the above molecular formula is replaced with Na, the electrical storage property is improved.

[0043] That is, the power storage material of the present invention is characterized in that it has a fiber material (fiber) and has countless concave and convex surfaces, and the fiber material is mainly composed of fibers from at least one of wood, plant fiber (pulp), animals, algae, microorganisms and microbial products.

[0044] The term "fibrous material having wood or plant fibers (pulp) or the like as main components" means a fibrous material containing the first component having cellulose fibers contained in wood or plant fibers or the like as primary components at the largest mass ratio.

[0045] For the power storage material of the present invention, the fiber material is preferably a crystallized amorphous fiber. It is particularly preferred that the crystallized amorphous fiber is arranged in a sheet shape. In addition, the fiber material may be an amorphous fiber having atomic vacancies. In addition, the diameter of the countless concavoconvexities is preferably 1 nm to 500 nm.

[0046] The electric storage material of the present invention can store and discharge electricity by utilizing the physical electron adsorption phenomenon based on the quantum size effect generated on the convex parts of the plurality of concave and convex parts. The countless concave and convex surfaces of the electric storage material of the present invention each form a capacitor composed of a solid / solid double electric layer, and these multiple capacitors form an electric distributed parameter circuit connected in parallel with a limited connection. As a result, the electric storage material of the present invention can store electricity in an instant or in a relatively short time, thereby enabling large-capacity electricity storage.

[0047] For the storage material of the present invention, as long as fine concavo-convex can be formed on the surface of the substrate, the crystallized / amorphous fiber material is not particularly limited. As examples of crystallized / amorphous fiber materials, cellulose fibers, chitin fibers, collagen fibers, etc. can be used. In addition, as cellulose fibers, pulp or cellulose nanofibers (hereinafter sometimes referred to as "CNF") are preferably used. Nano-sized CNF can improve the electron adsorption capacity based on the quantum size effect of the negative sixth method, and can increase the work function, thereby further increasing the storage capacity. In addition, since pulp is made of CNF, there are countless nano-scale concavo-convex on the surface of the pulp. Therefore, for the convenience of operation and process, pulp can be used directly.

[0048] [Cellulose fiber]

[0049] For the power storage material of the present invention, the type of cellulose fiber is not particularly limited, and for example, cellulose derived from plants (e.g., wood, bamboo, hemp, jute, kenaf, farm waste, cloth, pulp (coniferous unbleached sulfate pulp (NUKP), coniferous bleached sulfate pulp (NBKP), hardwood unbleached sulfate pulp (LUKP), hardwood bleached sulfate pulp (LBKP), coniferous unbleached sulfite pulp (NUSP), coniferous bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), recycled pulp, waste paper, etc.)), animals (e.g., ascidian), algae, microorganisms (e.g., acetic acid bacteria (Acetobacter)), microbial products, etc. can be used. Cellulose fibers derived from plants or microorganisms are preferred, and cellulose fibers derived from plants are more preferred.

[0050] There is no particular restriction on the number average fiber diameter of the cellulose raw material. In the case of softwood kraft pulp, which is a common pulp, the number average fiber diameter is about 30 to 60 μm, and in the case of hardwood kraft pulp, the number average fiber diameter is about 10 to 30 μm. In the case of other pulps, the number average fiber diameter of the pulp after normal refining is about 50 μm. For example, in the case of pulp obtained by refining a material of several centimeters in size such as debris, it is preferred to use a disintegrator such as a disc refiner or a beater to perform mechanical treatment so as to adjust the number average fiber diameter to about 50 μm.

[0051] [Cellulose nanofibers]

[0052] For the storage material of the present invention, the cellulose nanofibers may be unmodified cellulose nanofibers or chemically modified cellulose nanofibers. Examples of chemically modified cellulose nanofibers (chemically modified CNF) include anion-modified CNF, cation-modified CNF, etc., but anion-modified CNF is preferred. Anion-modified CNF refers to fine fibers obtained by defibrillating anion-modified cellulose fibers having anionic groups introduced into cellulose molecular chains to nanometer-scale fiber diameters.

[0053] As anion modified cellulose fibers, for example, carboxylated (oxidized) cellulose fibers, carboxymethylated cellulose fibers, phosphated cellulose fibers, and phosphite cellulose fibers can be listed. By defibration of these fibers, oxidized cellulose nanofibers, carboxymethylated cellulose nanofibers, phosphated cellulose nanofibers, and phosphite cellulose nanofibers can be obtained, respectively. Among them, carboxylated (oxidized) cellulose nanofibers and carboxymethylated cellulose nanofibers are preferred.

[0054] In this specification, "CNF" refers to a fiber with a fiber diameter of about 1 to 500 nm obtained by refining pulp or the like as a cellulose raw material to the nanoscale level. The average fiber diameter and average fiber length of cellulose nanofibers can be obtained by observing each fiber using an atomic force microscope (AFM) or a transmission electron microscope (TEM) and averaging the fiber diameter and fiber length obtained from the observation results. Cellulose nanofibers can be obtained by applying mechanical force to pulp for refining, or by defibration of anionic modified cellulose fibers such as carboxylated cellulose fibers (hereinafter, also referred to as "oxidized cellulose fibers"), carboxymethylated cellulose fibers, phosphated cellulose fibers, and phosphite cellulose fibers. The average fiber length and average fiber diameter of the fine fibers can be adjusted by oxidation treatment and defibration treatment.

[0055] The average aspect ratio of the cellulose nanofibers is usually not less than 50. The upper limit is not particularly limited, but is usually not more than 1000. The average aspect ratio can be calculated by the following formula.

[0056] Aspect ratio = average fiber length / average fiber diameter

[0057] The type of cellulose (hereinafter also referred to as "cellulose raw material") used as a raw material of anion-modified CNF is not particularly limited, and for example, cellulose derived from plants (e.g., wood, bamboo, hemp, jute, kenaf, agricultural waste, cloth, pulp (coniferous unbleached kraft pulp (NUKP), coniferous bleached kraft pulp (NBKP), hardwood unbleached kraft pulp (LUKP), hardwood bleached kraft pulp (LBKP), coniferous unbleached sulfite pulp (NUSP), coniferous bleached sulfite pulp (NBSP), thermomechanical pulp (TMP), recycled pulp, waste paper, etc.)), animals (e.g., ascidian species), algae, microorganisms (e.g., acetic acid bacteria (Acetobacter)), microbial products, etc. can be used. Cellulose fibers derived from plants or microorganisms are preferred, and cellulose fibers derived from plants are more preferred.

[0058] There is no particular restriction on the number average fiber diameter of the cellulose raw material. In the case of softwood kraft pulp, which is a common pulp, the number average fiber diameter is about 30 to 60 μm, and in the case of hardwood kraft pulp, the number average fiber diameter is about 10 to 30 μm. In the case of other pulps, the number average fiber diameter of the pulp after normal refining is about 50 μm. For example, in the case of pulp obtained by refining a material of several centimeters in size such as debris, it is preferred to use a disintegrator such as a disc refiner or a pulper to perform mechanical treatment to adjust to about 50 μm.

[0059] [Chemical modification]

[0060] Anionic modified cellulose fibers are prepared by introducing anionic groups into the above-mentioned cellulose raw materials. The method for introducing anionic groups is not particularly limited, and examples thereof include methods for introducing anionic groups into the pyranose ring of cellulose by oxidation or substitution reaction. Specifically, examples thereof include a reaction in which the hydroxyl group of the pyranose ring is oxidized to be converted into a carboxyl group, or a reaction in which a carboxylmethyl group, a phosphate group, or a phosphite group is introduced into the pyranose ring by substitution reaction.

[0061] [Carboxymethylation]

[0062] As mentioned above, as an example of anionic modification, carboxymethylation can be cited. Carboxymethylated cellulose fiber, as an example of anionic modified cellulose fiber, can be obtained by carboxymethylating the above-mentioned cellulose raw material by a known method, and can also be a commercial product. In either case, the degree of carboxymethyl substitution of each anhydroglucose unit of cellulose is 0.010 to 0.50, preferably 0.01 to 0.44, more preferably 0.02 to 0.40, and further preferably 0.10 to 0.30. In addition, if the degree of carboxymethyl substitution exceeds 0.50, it will dissolve in a medium such as water and may not be able to maintain a fibrous shape. The degree of carboxymethyl substitution of carboxymethylated cellulose fiber is the same value as the degree of carboxymethyl substitution of carboxymethylated cellulose nanofiber.

[0063] The carboxymethyl substitution degree of carboxymethylated cellulose fiber can be measured by the following method. That is, first, accurately weigh about 2.0g of carboxymethylated cellulose fiber (absolutely dry) and put it into a 300mL stoppered conical flask. Add 100mL of nitric acid methanol (a solution made by adding 100mL of extra-grade concentrated nitric acid to 1000mL of methanol) and shake for 3 hours to convert the carboxymethylated cellulose fiber (hereinafter also referred to as "CM cellulose fiber") in the form of a salt into an acid-type CM cellulose fiber. Accurately weigh 1.5-2.0g of acid-type CM cellulose fiber (absolutely dry) and put it into a 300mL stoppered conical flask. Wet the acid-type CM cellulose fiber with 15mL of 80% by mass methanol, add 100mL of 0.1N NaOH, and shake at room temperature for 3 hours. Use phenolphthalein as an indicator and back-titrate the excess NaOH with 0.1N H2SO4. The carboxymethyl substitution degree (DS) is calculated using the following formula.

[0064] A = [(100 × F'-(0.1N H2SO4) (mL) × F) × 0.1] / (absolute dry mass of acid-type CM cellulose fiber (g))

[0065] DS = 0.162 × A / (1-0.058 × A)

[0066] Wherein, A: the amount of 1N NaOH required to neutralize 1g of acid-type CM-modified cellulose fibers (mL), F: the correction factor of 0.1N H2SO4, and F': the correction factor of 0.1N NaOH.

[0067] As an example of a method for producing carboxymethylated cellulose fibers, the following method can be cited. That is, first, water and / or lower alcohols (e.g., water, methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol) are added to the cellulose raw material in a single or mixed medium in an amount of 3 to 20 times by weight as a solvent. In addition, the mixing ratio of the lower alcohols when mixed in the solvent for use is preferably 60 to 95% by mass. An alkali metal hydroxide (e.g., sodium hydroxide, potassium hydroxide) is added thereto in an amount of 0.5 to 20 times the anhydroglucose residue of the cellulose raw material in molar conversion as a mercerizing agent. The cellulose raw material is mixed with the solvent and the mercerizing agent, and mercerization treatment is performed at a reaction temperature of 0 to 70° C. (preferably 10 to 60° C.) and a reaction time of 15 minutes to 8 hours (preferably 30 minutes to 7 hours). Then, a carboxymethylating agent (e.g., monochloroacetic acid or a salt thereof) is added in an amount of 0.05 to 10.0 times the amount of the glucose residue in terms of mole, and an etherification reaction is carried out at a reaction temperature of 30 to 90° C. (preferably 40 to 80° C.) and a reaction time of 30 minutes to 10 hours (preferably 1 to 4 hours).

[0068] "Carboxymethylated cellulose fiber" as an anionically modified cellulose used to prepare anionically modified CNF refers to a fiber that can maintain at least a portion of its fibrous shape even when dispersed in water. Therefore, it is different from the above-mentioned carboxymethyl cellulose as a water-soluble polymer. If an aqueous dispersion of "carboxymethylated cellulose fiber" is observed with an electron microscope, a fibrous substance can be observed. On the other hand, even if an aqueous dispersion of carboxymethyl cellulose as a water-soluble polymer is observed, a fibrous substance cannot be observed. In addition, when "carboxymethylated cellulose fiber" is measured by X-ray diffraction, the peak of cellulose type I crystals can be observed, but cellulose type I crystals cannot be seen in carboxymethyl cellulose as a water-soluble polymer.

[0069] [Carboxylation (oxidation)]

[0070] As an example of anionic modification, carboxylation (also referred to as oxidation) can be cited. Carboxylation refers to a reaction in which the hydroxyl groups of the pyranose ring of cellulose are oxidized and converted into carboxyl groups (referring to -COOH (acid type) or -COOM (metal salt type) (M is a metal ion)). In this specification, anionic modified cellulose fibers obtained by carboxylation are also referred to as carboxylated cellulose fibers or oxidized cellulose fibers. Carboxylated cellulose fibers can be obtained by carboxylating (oxidizing) the above-mentioned cellulose raw material by a known method.

[0071] The amount of carboxyl groups in the carboxylated cellulose fibers is not particularly limited, but is preferably adjusted to 0.6 to 3.0 mmol / g, more preferably 1.0 to 2.0 mmol / g, relative to the absolute dry mass of the carboxylated cellulose fibers. The amount of carboxyl groups can be adjusted by controlling the type or amount of the oxidant, the temperature or time during the oxidation reaction, etc. The amount of carboxyl groups in the carboxylated cellulose fibers is the same as the amount of carboxyl groups in the carboxylated cellulose nanofibers.

[0072] The carboxyl group content of the carboxylated cellulose fiber can be measured by the following method. That is, first, 60 ml of a 0.5 mass % slurry of the carboxylated cellulose fiber (medium: water) is prepared, and a 0.1 M hydrochloric acid aqueous solution is added to adjust the pH to 2.5. A 0.05 N sodium hydroxide aqueous solution is added dropwise, and the conductivity is measured until the pH reaches 11. The carboxyl group content is calculated using the following formula from the amount of sodium hydroxide (a) consumed in the weak acid neutralization stage in which the conductivity changes slowly.

[0073] Carboxyl group content 〔mmol / g carboxylated cellulose fiber〕=a〔ml〕×0.05 / mass of carboxylated cellulose fiber〔g〕

[0074] As an example of the carboxylation (oxidation) method, there can be cited a method of oxidizing a cellulose raw material in water using an oxidant in the presence of an N-oxyl compound and a compound selected from the group consisting of bromide, iodide and a mixture thereof. Through this oxidation reaction, the primary hydroxyl group at the C6 position of the pyranose glucopyranose ring on the surface of the cellulose is selectively oxidized, thereby obtaining a cellulose fiber having an aldehyde group and a carboxyl group (-COOH) or a carboxylate group (-COO-) on the surface. The concentration of the cellulose raw material in water during the reaction is not particularly limited, but is preferably 5% by mass or less.

[0075] N-oxyl compounds refer to compounds that can generate nitroxide free radicals. As N-oxyl compounds, any compound can be used as long as it is a compound that promotes the target oxidation reaction. For example, 2,2,6,6-tetramethylpiperidin-1-oxyl radical (TEMPO) and its derivatives (for example, 4-hydroxy TEMPO) can be listed. The amount of N-oxyl compound used is not particularly limited as long as it is a catalytic amount that can oxidize the cellulose raw material. For example, relative to 1g of absolutely dry cellulose raw material, the amount of N-oxyl compound used is preferably 0.01 to 10mmol, more preferably 0.01 to 1mmol, and further preferably 0.05 to 0.5mmol. In addition, relative to the total amount of the reaction solution, it can be about 0.1 to 4mmol / L.

[0076] Bromide refers to a compound containing bromine, and examples thereof include bromides of alkali metals that can be dissociated in water and ionized. In addition, iodide refers to a compound containing iodine, and examples thereof include iodides of alkali metals. The amount of bromide or iodide used can be selected within the range that can promote the oxidation reaction. For example, the total amount of bromide and iodide is preferably 0.1 to 100 mmol, more preferably 0.1 to 10 mmol, and further preferably 0.5 to 5 mmol relative to 1 g of absolutely dry cellulose raw material.

[0077] As the oxidant, a known oxidant can be used, for example, a halogen, hypohalous acid, halogenous acid, perhalogen acid or its salt, halogen oxide, peroxide can be used. Among them, sodium hypochlorite, which is inexpensive and has a small environmental load, is preferred. For example, the appropriate amount of the oxidant is preferably 0.5 to 500 mmol, more preferably 0.5 to 50 mmol, further preferably 1 to 25 mmol, and further preferably 3 to 10 mmol relative to 1 mol of the N-oxyl compound. In addition, for example, the appropriate amount of the oxidant is preferably 1 to 40 mol relative to 1 mol of the N-oxyl compound.

[0078] Even under relatively mild conditions, the oxidation of the cellulose raw material can react efficiently. Therefore, the reaction temperature can be 4 to 40°C, or room temperature of about 15 to 30°C. As the reaction proceeds, carboxyl groups are generated on the cellulose chains, so a decrease in the pH of the reaction solution can be confirmed. In order to efficiently carry out the oxidation reaction, it is preferred to add an alkaline solution such as an aqueous sodium hydroxide solution to keep the pH of the reaction solution at 8 to 12, preferably at about 10 to 11. From the perspective of easy handling or less prone to side reactions, the medium in the reaction solution is preferably water. The reaction time in the oxidation reaction can be appropriately set according to the degree of oxidation, and is generally 0.5 to 6 hours, for example, about 0.5 to 4 hours.

[0079] The oxidation reaction may be carried out in two stages. For example, the oxidized cellulose fibers obtained by filtering after the first stage reaction are oxidized again under the same or different reaction conditions, thereby allowing efficient oxidation without being inhibited by the reaction of the byproduct salt generated in the first stage reaction.

[0080] As another example of the carboxylation (oxidation) method, there is a method of contacting a cellulose raw material with an ozone-containing gas to perform oxidation. By this oxidation reaction, at least the hydroxyl groups at positions 2 and 6 of the pyranose glucopyranose ring are oxidized to carboxyl groups, and the cellulose chain is decomposed. The ozone concentration in the ozone-containing gas is preferably 50 to 250 g / m 3 , more preferably 50 to 220 g / m 3. When the solid content of the cellulose raw material is set to 100 parts by mass, the amount of ozone added to the cellulose raw material is preferably 0.1 to 30 parts by mass, and more preferably 5 to 30 parts by mass. The ozone treatment temperature is preferably 0 to 50°C, and more preferably 20 to 50°C. The ozone treatment time is not particularly limited, but can be about 1 to 360 minutes, and preferably about 30 to 360 minutes. If the conditions of the ozone treatment are within these ranges, excessive oxidation and decomposition of cellulose can be prevented, and the yield of oxidized cellulose fibers is good.

[0081] After the ozone treatment, an additional oxidation treatment may be performed using an oxidant. The oxidant used in the additional oxidation treatment is not particularly limited, but includes chlorine compounds such as chlorine dioxide and sodium chlorite, oxygen, hydrogen peroxide, persulfuric acid, and peracetic acid. For example, the additional oxidation treatment may be performed by dissolving these oxidants in a polar organic solvent such as water or alcohol to prepare an oxidant solution and immersing the cellulose raw material in the solution.

[0082] [Esterification]

[0083] As an example of anionic modification, esterification can be cited. As an example of esterification, introduction of a phosphate group or a phosphite group into a cellulose raw material can be cited. In this specification, anionic modified cellulose fibers obtained by introducing a phosphate group are referred to as "phosphated cellulose fibers", and anionic modified cellulose fibers obtained by introducing a phosphite group are referred to as "phosphite-esterified cellulose fibers", and both are collectively referred to as "esterified cellulose fibers".

[0084] As a method for producing phosphated cellulose fibers, there can be cited a method of mixing a powder or aqueous solution of a compound having a phosphate group into a cellulose raw material or a slurry thereof. As the compound having a phosphate group, there can be cited phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, ammonium metaphosphate, etc. These compounds can be used alone or in combination of two or more.

[0085] The addition ratio of the compound having a phosphate group to the cellulose raw material is preferably 0.1 to 500 parts by mass, more preferably 1 to 400 parts by mass, and further preferably 2 to 200 parts by mass, relative to 100 parts by mass of the solid content of the cellulose raw material, calculated as the amount of addition of phosphorus element. The reaction temperature is preferably 0 to 95°C, more preferably 30 to 90°C. The reaction time is not particularly limited, but is about 1 to 600 minutes, more preferably 30 to 480 minutes. From the perspective of inhibiting cellulose hydrolysis, it is preferred that the suspension of the obtained phosphated cellulose fiber is dehydrated and then heat-treated at 100 to 170°C. The degree of substitution of the phosphate group of each glucose unit of the phosphated cellulose fiber is preferably 0.001 or more and less than 0.40.

[0086] As a method for producing phosphite-esterified cellulose fibers, there can be cited a method of adding a substance containing alkali metal ions and an additive (A) (preferably sodium hydrogen phosphite) composed of at least one of phosphorous acids and metal phosphites to a cellulose raw material or its slurry, and heating, thereby introducing phosphite groups containing cations formed by inorganic substances into the cellulose fibers. In addition, a method of adding an additive (B) composed of at least one of urea and urea derivatives, and heating, thereby introducing phosphite groups and carbamate groups containing cations formed by inorganic substances into the cellulose fibers is more preferred. As substances containing alkali metal ions, for example, hydroxides, metal sulfates, metal nitrates, metal chlorides, metal phosphates, metal phosphites, and metal carbonates can be used. However, metal phosphites that also serve as additives (A) are preferred, and sodium hydrogen phosphite is more preferred.

[0087] The additive (A) is composed of at least one of phosphorous acids and metal phosphites. As the additive (A), for example, phosphorous acid, sodium hydrogen phosphite, ammonium hydrogen phosphite, potassium hydrogen phosphite, sodium dihydrogen phosphite, sodium phosphite, lithium phosphite, potassium phosphite, magnesium phosphite, calcium phosphite, triethyl phosphite, triphenyl phosphite, pyrophosphorous acid and other phosphorous acid compounds can be used. These phosphorous acids or metal phosphites can be used alone or in combination. However, sodium hydrogen phosphite, which also serves as a substance containing alkali metal ions, is preferred. The amount of additive (A) added is preferably 1 to 10,000 g, more preferably 100 to 5,000 g, and further preferably 300 to 1,500 g relative to 1 kg of cellulose raw material.

[0088] The additive (B) is composed of at least any one of urea and urea derivatives. As the additive (B), for example, urea, thiourea, biuret, phenylurea, benzylurea, dimethylurea, diethylurea, tetramethylurea can be used. These ureas or urea derivatives can be used alone or in combination. However, urea is preferably used. The amount of additive (B) added is preferably 0.01 to 100 mol, more preferably 0.2 to 20 mol, and further preferably 0.5 to 10 mol relative to 1 mol of the additive (A).

[0089] The reaction temperature is preferably 100 to 200° C., more preferably 100 to 180° C. The reaction time is not particularly limited, but is about 10 to 180 minutes, more preferably 30 to 120 minutes. The cellulose fibers into which phosphite groups and the like are introduced are preferably washed before defibration. The degree of substitution of the phosphite groups per glucose unit of the phosphite-esterified cellulose fibers is preferably 0.01 or more and less than 0.23.

[0090] [Fiberization]

[0091] The device for defibration of the anionically modified cellulose fibers is not particularly limited, but it is preferred to use a high-speed rotary type, a colloid mill type, a high pressure type, a roller mill type, an ultrasonic type and the like device to apply a strong shear force to the dispersion of the anionically modified cellulose fibers. In order to efficiently defibrate, it is preferred to use a wet high pressure or ultra-high pressure homogenizer that can apply a pressure of more than 50MPa to the dispersion of the anionically modified cellulose fibers and can apply a strong shear force. The pressure is more preferably more than 100MPa, and more preferably more than 140MPa. The number of times of treatment (passing) with the defibration device can be 1 or more than 2 times, preferably more than 2 times.

[0092] In the dispersion treatment, the anionically modified cellulose fibers are usually dispersed in a solvent. The solvent is not particularly limited as long as it is a solvent that can disperse the anionically modified cellulose fibers, and examples thereof include water, organic solvents (for example, hydrophilic organic solvents such as methanol), and mixed solvents of these solvents. Since the anionically modified cellulose fibers are hydrophilic, the solvent is preferably water.

[0093] The solid content concentration of the anionically modified cellulose fibers in the dispersion is usually 0.1% by weight or more, preferably 0.2% by weight or more, and more preferably 0.3% by weight or more. Thus, the amount of liquid relative to the amount of the anionically modified cellulose fibers reaches an appropriate and effective amount. The upper limit is usually 10% by weight or less, preferably 6% by weight or less. Thus, fluidity can be maintained.

[0094] Furthermore, the anionically modified cellulose fibers may be pretreated as needed before the defibration and dispersion treatment using a high-pressure homogenizer. The pretreatment may be performed using a mixing, stirring, emulsifying, or dispersing device such as a high-speed shear mixer.

[0095] The anion modified cellulose fiber may be in the state of a water dispersion obtained after manufacture, or may be subjected to post-treatment as required. As post-treatment, for example, drying (for example, freeze drying, spray drying, shelf drying, drum drying, belt drying, a method of thinly spreading on a glass plate or the like for drying, fluidized bed drying, microwave drying, heating fan type reduced pressure drying), redispersion in water (dispersing device is not limited), pulverization (for example, pulverization using equipment such as a chopper, hammer mill, pin mill, air flow pulverizer, etc.), but it is not particularly limited.

[0096] In order to achieve the desired weight reduction effect, the sheet thickness of the power storage material of the present invention is preferably 100 μm or less, preferably 50 μm or less, in the form of a thin film. In this case, since static charge attaches and detaches on the surface, the power density and energy density can be increased by making it into a thin film.

[0097] The electric storage material of the present invention has a resistance of 100 MΩ or more, more preferably 100 GΩ or more, and a capacitance of 5 mF / cm 2 More than. In addition, it is preferably capable of long-term discharge of more than 1 day by instantaneous or short-time storage of 1ms to 1 minute and large-capacity storage. In addition, it is preferably capable of fast response charging and discharging of 1mHz to 100kHz, and more preferably capable of fast response charging and discharging of 0.1 to 100Hz. It can be considered that the storage material of the present invention can store the current from the generator every 50 / 1000 to 60 / 1000 seconds by converting 50Hz and 60Hz alternating current into direct current using an AC / DC converter. As a result, solid storage bodies can be transported without power transmission lines, and can be freely transported at home and abroad not only by cars but also by ships, airplanes, etc.

[0098] In order to enhance the quantum size effect, the specific surface area of ​​the fiber material of the power storage material of the present invention is preferably 10 m 2 / g or more, more preferably 100m 2 / g or more, more preferably 300m 2 / g or more. Thus, the storage material of the present invention can store electricity in an instant or in a relatively short time, and can store electricity in large capacity. In addition, a capacitor whose specific surface area is larger than that of a conventional capacitor and whose storage system is composed of a double electric layer is usually referred to as a supercapacitor, and a capacitor with a storage capacity of more than three digits is further referred to as an ultracapacitor.

[0099] The specific surface area of ​​a fiber material such as cellulose fiber used in the power storage material of the present invention can be measured by the method according to the following procedures (1) to (9) with reference to the nitrogen adsorption method (JIS Z 8830).

[0100] (1) A slurry of about 3% cellulose fibers (dispersion medium: water) was prepared so as to have a solid content of about 0.1 g, placed in a centrifugal separation container, and 100 ml of ethanol was added.

[0101] (2) The mixture was stirred in the container at 3000 rpm for 30 minutes using a Homodisper Model 2.5 (manufactured by PRIMIX Corporation).

[0102] (3) After stirring, the cellulose fibers were allowed to settle in a centrifuge at 7000 G, 30 minutes, and 30°C.

[0103] (4) The supernatant is removed in such a way as to avoid removing the settled cellulose fibers as much as possible.

[0104] (5) After removing the supernatant, add 100 ml of ethanol, and further repeat the stirring under the conditions of step (2), the centrifugal separation under the conditions of step (3), and the removal of the supernatant under the conditions of step (4) three times.

[0105] (6) The solvent in step (5) is replaced by tert-butyl alcohol from ethanol, and the same method as step (5) is repeated three times at room temperature above the melting point of tert-butyl alcohol, followed by stirring, centrifugation, and removal of the supernatant.

[0106] (7) Finally, after removing the supernatant, add 30 ml of tert-butyl alcohol and mix gently, transfer to a conical tube, and freeze with liquid nitrogen.

[0107] (8) The conical tube was installed in a freeze dryer and freeze-dried for 3 days.

[0108] (9) Then, BET measurement was performed (pretreatment conditions: nitrogen flow, 105° C., 2 hours, relative pressure 0.01 to 0.30, sample amount about 30 mg).

[0109] The super-electric accumulator of the present invention is characterized in that it has the electric storage material of the present invention. For the super-electric accumulator of the present invention, it is preferred that the electric storage material is in the form of a thin film sheet and has an electric storage body, wherein the electric storage body has a pair of metal electrodes respectively arranged on both sides of the electric storage material in a manner of clamping the electric storage material. In this case, it is equivalent to a distributed parameter capacitor having a plurality of tiny capacitors perpendicular to each metal electrode corresponding to the number of concave and convex portions. That is, the tiny concave and convex portions themselves form a high resistance, which can be represented by a parallel equivalent circuit of C and R. In addition, the super-electric accumulator of the present invention can be manufactured by using a micro-electromechanical system (MEMS or NEMS) and forming upper and lower conductive electrodes composed of Al, Cu, gold, polyacetylene, etc. by sputtering or casting. At this time, it is preferred that each conductive electrode covers the convex surface along the surface shape of the electric storage portion. In addition, it is preferred that the super-electric accumulator of the present invention can operate at -269°C to 300°C.

[0110] The super accumulator of the present invention can be composed of a stacked body obtained by stacking a plurality of the accumulators. In this case, for example, various MEMS methods can be used to stack in parallel, and each parallel equivalent circuit can be made into a solid quantum direct accumulator in which each parallel equivalent circuit is combined in the form of an electrical distribution parameter. In addition, the super accumulator of the present invention can also be composed of a parallel integrated body in which a plurality of the accumulator materials are arranged along the inner side of each metal electrode between each metal electrode. In this case, a withstand voltage of more than 1GV / m can be obtained.

[0111] The super power storage body of the present invention can be used as an AC capacitor for microelectronic circuits or a power storage body on the back of a solar panel. In addition, it can also be applied to various backup power modules, or coupling elements, noise filters, high-sensitivity acceleration sensors, high-power transformer anti-break devices, emergency power supply devices for automobiles or ships, and other electronic and electrical substrates. In the future, it is also expected to be used as a DC power storage material that directly stores sunlight from outer space.

[0112] The following five conditions exist as physical power storage conditions using a solid as a power storage body.

[0113] (1) In order to produce the quantum size effect, the surface has an uneven surface with a thickness of less than 20 nm.

[0114] (2) Materials with high work function (electron adsorption capacity)

[0115] (3) Structure with local positive charge

[0116] (4) The surface circuit is formed into an electrically distributed parameter circuit (parallel connection) (charge accumulation effect)

[0117] (5) The resistance is as high as 100 MΩ or more to avoid leakage of stored charge.

[0118] The power storage material and super power storage body of the present invention can simultaneously satisfy these five conditions and have excellent performance as a solid quantum power storage material and quantum power storage body.

[0119] Effects of the Invention

[0120] According to the present invention, it is possible to provide a power storage material and a super power storage body which are produced by using a fiber material of cellulose molecules obtained from wood or plant fibers (pulp) and which are capable of storing electricity under direct current and alternating current. BRIEF DESCRIPTION OF THE DRAWINGS

[0121] Figure 1 This is a perspective view showing the molecular structure of the power storage material according to the embodiment of the present invention.

[0122] Figure 2 This is a circuit diagram showing an electric distribution parameter circuit of an electric storage material according to an embodiment of the present invention.

[0123] Figure 3 This is an atomic force microscope (AFM) image of the surface of Sample 1 which is the electricity storage material according to the embodiment of the present invention.

[0124] Figure 4 This is a graph showing the discharge characteristics of Sample 1, which is the electricity storage material according to the embodiment of the present invention, at a constant current of 1 nA after being charged at 1 mA and 10 V.

[0125] Figure 5 This is a graph showing the relationship between the load voltage and the stored energy during charging of Sample 2, which is the electricity storage material according to the embodiment of the present invention.

[0126] Figure 6 Graph showing the frequency characteristics of the storage capacity Cp of Sample 2, which is the storage material according to the embodiment of the present invention, when connected in series.

[0127] Figure 7 It is a Nyquist plot (Cole-Cole plot) showing the AC impedance of the frequency characteristic of the sample 3 which is the power storage material according to the embodiment of the present invention.

[0128] Figure 8 The following are a side view and a perspective view showing a method for producing a stacked body of a super power storage body according to an embodiment of the present invention by a MEMS method. DETAILED DESCRIPTION

[0129] Hereinafter, the power storage material and the super power storage body according to the embodiment of the present invention will be described based on the drawings and examples.

[0130] like Figure 1As shown, the power storage material according to the embodiment of the present invention is a sheet having a numerous concavo-convex surface and composed of crystallized / amorphous fibers having wood fibers (pulp) as a main component.

[0131] The power storage material of the embodiment of the present invention can store and discharge electricity by utilizing the electron adsorption phenomenon based on the quantum size effect generated on the countless concave and convex parts. The countless concave and convex surfaces of the power storage material of the embodiment of the present invention each form a capacitor composed of a solid / solid double layer, such as Figure 2 The plurality of capacitors shown form an electric distributed parameter circuit connected in parallel in a limited manner. Thus, the electric storage material according to the embodiment of the present invention can store electricity instantaneously or in a relatively short period of time, and can store electricity of a large capacity.

[0132] Examples of the power storage material and super power storage body according to the embodiment of the present invention are shown below. Note that the following examples are provided only for the purpose of illustrating the present invention and for reference to specific forms, and do not limit or restrict the scope of the invention disclosed in this application.

[0133] Example 1

[0134] The electric storage material of the embodiment of the present invention was manufactured. Table 1 shows the manufacturing method, processing method, manufacturing conditions, density, resistance (GΩ), and storage capacity (F / cm2) of the electric storage materials of samples 1 to 4 manufactured. 2 The charge capacity is calculated by charging at 1 mA for 4 minutes and then discharging at a constant current of 1 nA (see, for example, Figure 4 ), the resistance is obtained from the Nyquist plot (see, for example, Figure 6 Each of the samples 1 to 4 was produced in the following manner.

[0135] <Sample 1>

[0136] 500 g (absolutely dry) of bleached unbeaten kraft pulp (brightness 85%) from softwood is added to 500 ml of an aqueous solution containing 780 mg of TEMPO (Sigma-Aldrich) and 75.5 g of sodium bromide, and stirred until the pulp is evenly dispersed. An aqueous sodium hypochlorite solution is added to the reaction system to a concentration of 6.0 mmol / g to start the oxidation reaction. During the reaction, the pH in the system decreases, and 3 M aqueous sodium hydroxide solution is added successively to adjust the pH to 10. When the sodium hypochlorite is consumed and the pH in the system no longer changes, the reaction is completed. The reaction mixture is filtered through a glass filter to separate the pulp, and the pulp is washed thoroughly with water to obtain an oxidized pulp (hereinafter referred to as "TEMPO oxidized pulp"). The pulp yield at this time is 90%, and the time required for the oxidation reaction is 90 minutes. In addition, the specific surface area of ​​the obtained TEMPO oxidized pulp is 53 m2 / g.

[0137] The TEMPO oxidized pulp obtained by the above process was adjusted to 3.0% (w / v) with water and subjected to five defibration treatments using an ultra-high pressure homogenizer (20°C, 150 MPa) to obtain a TEMPO oxidized fine cellulose fiber dispersion (hereinafter referred to as "TEMPO oxidized CNF"). The average fiber diameter of the obtained TEMPO oxidized CNF was 4 nm, and the aspect ratio was 150. The carboxyl group content of the obtained TEMPO oxidized CNF was 1.42 mmol / g. In addition, the specific surface area of ​​the obtained TEMPO oxidized CNF was 386 m 2 / g.

[0138] To the obtained 3% (w / v) TEMPO oxidized CNF dispersion, ion exchange water was added and stirred at 3000 rpm for 10 minutes using a homogenizer to dilute to a concentration of 0.5% (w / v). The dispersion was depressurized with an aspirator to deaerate the dispersion, and further degassed with MAZERUSTAR-KK-300SS (manufactured by Kurabo Industries Ltd.) at 2000 rpm for 2 minutes. Then, a mold frame (100 cm 2 ) was placed on a hydrophilic polyethylene terephthalate film, 140 g of the dispersion was poured into the mold frame, and dried at 40°C for 48 hours to obtain TEMPO oxidized CNF sheets.

[0139] <Sample 2>

[0140] A 3% (w / v) dispersion of TEMPO oxidized CNF prepared by the same method as Sample 1 was pressurized (heated) to 350°C in an autoclave and treated at a constant pressure of 25 MPa. Then, ion exchange water was added and the mixture was stirred at 3000 rpm in a homogenizer for 10 minutes to be diluted to a concentration of 0.5% (w / v). TEMPO oxidized CNF sheets were obtained by the same method as Sample 1.

[0141] <Sample 3>

[0142] The 90 cm filter with a mesh size of 63 μm was used for filtration. 2 20 g of the dispersion obtained by adding ion-exchanged water to the TEMPO-oxidized pulp obtained in the same manner as Sample 1 to adjust the concentration to 0.5% (w / v) was extracted with a nylon mesh and then dried at 40°C for 48 hours to obtain a TEMPO-oxidized pulp sheet.

[0143] <Sample 4>

[0144] 130 parts of water and 20 parts of sodium hydroxide dissolved in a mixed solvent of 10 parts of water and 90 parts of isopropyl alcohol (IPA) were added to a biaxial kneader with the rotation speed adjusted to 150 rpm, and 100 parts of hardwood pulp (LBKP manufactured by NIPPON PAPER INDUSTRIES CO., LTD.) were added in terms of dry mass when dried at 100°C for 60 minutes. Stirring and mixing at 35°C for 80 minutes, mercerization treatment was performed. Further stirring was performed, and a mixed solvent of 23 parts of water and 207 parts of IPA and 40 parts of sodium monochloroacetate were added at the same time. After stirring for 30 minutes, the temperature was raised to 70°C and etherification treatment was performed for 90 minutes. After the reaction was completed, acetic acid was used to neutralize to pH 7, and after washing with aqueous methanol, the liquid was removed, dried, and crushed to obtain the sodium salt of CM pulp. The degree of carboxymethyl ether substitution in the obtained CM pulp was 0.17.

[0145] The CM pulp obtained by the above process was adjusted to 3.0% (w / v) with water and subjected to five defibration treatments using an ultra-high pressure homogenizer (20°C, 150 MPa) to obtain a CM fine cellulose fiber dispersion (hereinafter referred to as "CM CNF"). The specific surface area of ​​the obtained CM CNF was 325 m 2 / g. Ion exchange water was added to the obtained 3.0% (w / v) CM-CNF dispersion, and the mixture was stirred at 3000 rpm for 10 minutes using a homogenizer to dilute the mixture to a concentration of 0.5% (w / v). The dispersion was decompressed with an aspirator to degas the dispersion, and further degassed with MAZERUSTAR-KK-300SS (manufactured by Kurabo Industries Ltd.) at 2000 rpm for 2 minutes. Then, a mold frame (100 cm 2 ) was placed on a hydrophilic polyethylene terephthalate film, 140 g of the dispersion was poured into the mold frame, and dried at 40°C for 48 hours to obtain a CM-type CNF sheet.

[0146] [Table 1]

[0147]

[0148] As shown in Table 1, it can be confirmed that the resistance of each of the electric storage materials of Samples 1 to 4 is 50 GΩ to 135 GΩ, and the electric capacity is 3 F / cm 2 ~19F / cm 2. In particular, since sample 2 is amorphous and therefore has atomic vacancies, it has a positive charge that increases the amount of electrons adsorbed and the amount of electricity stored. In addition, a low specific gravity of less than 2 was confirmed. In addition, it was confirmed that each of the energy storage materials of samples 1 to 4 can operate at -269°C to 300°C and 500V. In addition, a voltage resistance of up to 1,000V was confirmed. Based on the above, it can be considered that each energy storage material is a material that is particularly suitable for high-voltage fields or atmospheric current (lightning) energy storage. In addition, it was confirmed that when using 3mA / m 2 When sample 2 is irradiated with a strong electron beam, it has an electrical resistance of up to 200 keV, which is more than twice as high as 80 keV of carbon nanotubes.

[0149] Figure 3 An atomic force microscope (AFM) image of the surface of sample 1 is shown in FIG. Figure 3 As shown, it can be confirmed that there are countless concavities and convexities with a diameter of less than 3nm on the surface of the storage material. In addition, the characteristics of sample 1 after charging at 1mA and 10V and discharging at a constant current of 1nA were measured, and the results are shown in Figure 4 . Figure 4 Also shown in the figure are amorphous titanium dioxide ("titanium dioxide" in the figure) and amorphous perfluoropolymer ("polymer" in the figure) as comparative examples. Figure 4 As shown, it was confirmed that the discharge time of the amorphous titanium dioxide and the amorphous polymer was 10 seconds or less, and the discharge time (capacity storage) of the sample 1 was about 2370 seconds.

[0150] Example 2

[0151] The storage material of Sample 2 was used to charge for 2 seconds using a constant voltage method, which is different from the conventional lithium-ion rechargeable battery charging method which takes several hours based on constant current charging. The relationship between the load voltage and the storage energy at this time was measured and is shown in Figure 5 .like Figure 5 As shown in the figure, it can be confirmed that the charging voltage increases in a very short time and the storage capacity increases parabolically.

[0152] Example 3

[0153] The storage capacity of the sample 2 under AC and series connection was measured. Copper electrodes were mechanically fixed above and below the sample 2 film with a surface area of ​​10 mm × 30 mm, and the storage capacity in the frequency range of 1 mHz to 1 MHz was measured using a constant potential meter / constant current meter. The measurement results are shown in Figure 6 .

[0154] like Figure 6As shown, it can be confirmed that the storage capacity of the storage material of sample 2 increases logarithmically as the frequency decreases. This is considered to be because the storage material of the embodiment of the present invention is charged and discharged at the interface between nano-diameter fiber materials in the low-frequency region, but not at the interface between fiber materials with large height differences in the high-frequency region. In addition, the same phenomenon of increased capacitance in the low-frequency region can be observed in amorphous titanium dioxide (for example, see non-patent document 10).

[0155] As described above, the power storage material according to the embodiment of the present invention can be charged and discharged in a low frequency region by the quantum nanosize effect, and is considered to be useful in applications such as AC capacitors for microelectronic circuits and noise filters.

[0156] Example 4

[0157] The frequency characteristics were measured using the power storage material of Sample 3. Copper electrodes were mechanically fixed above and below the thin film of Sample 2 with a surface area of ​​10 mm × 30 mm. The Nyquist plot of AC impedance in the frequency range of 1 mHz to 1 GHz was measured and the results are shown in Figure 7 .

[0158] like Figure 7 As shown, the Nyquist plot parallel to the imaginary axis is obtained. Such AC impedance characteristics reflect the formation of a distributed parameter circuit with countless capacitors connected in parallel to the resistor R, reflecting the Figure 2 The electrical distributed parameter circuit shown forms a huge electrical storage body.

[0159] The characteristics of the storage material of the embodiment of the present invention are compared with the characteristics of commercially available lithium ion batteries and double-layer capacitors, and physical rechargeable batteries (battenice) under development, and the results are shown in Table 2. In addition, "○" in Table 2 indicates that the characteristics are relatively good, "×" indicates that the characteristics are relatively poor, and "△" indicates that the characteristics are at an average level. As shown in Table 2, the storage material of the embodiment of the present invention has superior characteristics relative to lithium ion batteries, especially in terms of charging voltage, operating temperature, charging time, DC storage, fire resistance, and environmental pollution. It has superior characteristics relative to double-layer capacitors, especially in terms of charging voltage, operating temperature, fire resistance, and environmental pollution. It has superior characteristics relative to physical rechargeable batteries, especially in terms of charging voltage, operating temperature, and DC storage.

[0160] [Table 2]

[0161]

[0162] Example 5

[0163] like Figure 8As shown in FIG. 1 , a stacked power storage body was produced by MEMS method using the supercapacitor material of sample 2. First, a Cu layer (thickness 500 nm) was formed on the surface of a glass substrate (40×40×0.5 mm) by sputtering (see FIG. 1 ). Figure 8 1), an Al layer is sputtered on the Cu layer (refer to Figure 8 3). The glass substrate is removed and used as a base body of a storage layer for an electronic circuit. In addition, the Cu layer and the Al layer form a pair of metal electrodes. Multiple sheets of them are stacked to produce a storage layer for an electronic circuit. For the stacked storage body produced, the Al layer of the top storage layer for an electronic circuit and the Cu layer of the bottom storage layer for an electronic circuit are used as terminals, and each storage layer for an electronic circuit is connected in parallel. Therefore, for example, a stacked body obtained by stacking 100 storage layers for an electronic circuit has a capacity 100 times the capacity of a single storage layer for an electronic circuit.

[0164] The power storage body of the embodiment of the present invention can be used as an AC capacitor for a microelectronic circuit or a power storage body on the back of a solar panel. In addition, it can also be applied to various backup power supply modules such as lightning arresters, welding, and over-discharge prevention, or electronic and electrical substrates such as coupling elements, noise filters, high-sensitivity acceleration sensors, high-power transformer disconnection prevention devices, and emergency power supply devices for automobiles or ships.

Claims

1. An electric storage material used in an electric storage body having a pair of conductive electrodes provided on both sides of an electric storage material in a thin film sheet-like manner, wherein: The invention has crystallized amorphous fibers and has a plurality of concavities and convexities with a diameter of 1 nm to 500 nm on the surface, wherein the crystallized amorphous fibers are mainly composed of fibers from at least one of wood, animals, algae, microorganisms and microbial products, and the specific surface area of ​​the crystallized amorphous fibers is 100 m 2 / g or above.

2. An electric storage material used in an electric storage body having a pair of conductive electrodes provided on both sides of an electric storage material in a manner of sandwiching a thin film sheet-shaped electric storage material, characterized in that: The invention has crystallized amorphous fibers and has a plurality of concavities and convexities with a diameter of 1 nm to 500 nm on the surface, wherein the crystallized amorphous fibers are mainly composed of fibers derived from plant fibers, and the specific surface area of ​​the crystallized amorphous fibers is 100 m 2 / g or above.

3. An electric storage material used in an electric storage body having a pair of conductive electrodes provided on both sides of an electric storage material in a thin film sheet-like manner, wherein: It has crystallized amorphous fibers and has a plurality of concavities and convexities with a diameter of 1 nm to 30 nm on the surface, wherein the crystallized amorphous fibers are mainly composed of fibers derived from at least any one of wood, animals, algae, microorganisms, and microorganism products.

4. An electric storage material used in an electric storage body having a pair of conductive electrodes provided on both sides of an electric storage material in a thin film sheet-like manner, wherein: The invention comprises crystallized amorphous fibers having a plurality of concavities and convexities with a diameter of 1 nm to 30 nm inclusive on the surface, wherein the crystallized amorphous fibers mainly comprise fibers derived from plant fibers.

5. The electric storage material according to claim 1, characterized in that The diameter of the concavities and convexities is greater than or equal to 1 nm and less than or equal to 30 nm.

6. The electric storage material according to claim 2, characterized in that The diameter of the concavities and convexities is greater than or equal to 1 nm and less than or equal to 30 nm.

7. The power storage material according to any one of claims 1 to 6, characterized in that The crystallized amorphous fibers are amorphous fibers having atomic vacancies.

8. The power storage material according to any one of claims 1 to 6, characterized in that The electrical storage material has a resistance of 100 MΩ or more and a capacitance of 5 mF / cm 2 above.

9. A super power storage body, characterized in that: It has: The electric storage material according to any one of claims 1 to 6 in the form of a thin film sheet, and A power storage body including a pair of conductive electrodes provided on both sides of the power storage material so as to sandwich the power storage material.

10. The super power storage body according to claim 9, characterized in that: The crystallized amorphous fibers are amorphous fibers having atomic vacancies.

11. The super power storage body according to claim 9, characterized in that: The electrical storage material has a resistance of 100 MΩ or more and a capacitance of 5 mF / cm 2 above.

12. The super power storage body according to claim 9, characterized in that: It is composed of a stacked body in which a plurality of the above-mentioned electricity storage bodies are stacked.

Citation Information

Patent Citations

  • Apparatus and method for measuring load resisting capacity for engine lubricant

    JP1989098945A

  • Power storage device and manufacturing method thereof

    JP2016134934A

  • Power storage material and power storage device

    JP2017041578A

  • Carboxymethyl cellulose nanofiber, method for manufacturing the same, and organism applicable material using carboxymethyl cellulose nanofiber

    JP2015000977A

  • Insulating material, passive element, circuit board, and method of manufacturing an insulating sheet

    US20150014039A1